2020
DOI: 10.1016/j.lwt.2020.109283
|View full text |Cite
|
Sign up to set email alerts
|

Correction of defective textures in packaged dry-cured pork ham by applying conventional and ultrasonically-assisted mild thermal treatments

Abstract: Pastiness is a textural defect characterized by an excessive softness and loss of elasticity which lacks corrective actions at industrial level. The objective of this study was to evaluate the textural and microstructural changes of dry-cured pork ham, with different pastiness levels, subjected to conventional and ultrasonically-assisted corrective mild thermal treatments. Pastiness was assessed by an expert sensory panel and hams were classified into three categories: high (HP), medium (MP) and no (NP) pastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Morales, Serra, Guerrero & Gou (2007) also found that BF muscles from pork dry-cured ham with levels of NaCl lower than 2% were more prone to show soft textures. Optimization of the Fenalår elaboration process and corrective actions using emerging technologies (Coll-Brasas, Arnau et al, 2019;Contreras et al, 2020) could help to yield SR and NNSR Fenalårs with similar textural characteristics to SS Fenalårs. Temperature of the air of the drying room where the hams were stored.…”
Section: Characterization Of Colour and Texturementioning
confidence: 99%
“…Morales, Serra, Guerrero & Gou (2007) also found that BF muscles from pork dry-cured ham with levels of NaCl lower than 2% were more prone to show soft textures. Optimization of the Fenalår elaboration process and corrective actions using emerging technologies (Coll-Brasas, Arnau et al, 2019;Contreras et al, 2020) could help to yield SR and NNSR Fenalårs with similar textural characteristics to SS Fenalårs. Temperature of the air of the drying room where the hams were stored.…”
Section: Characterization Of Colour and Texturementioning
confidence: 99%
“…Hence, studying the status of muscle fibers mainly including sarcomeres, Z line, A band, and I band have made it possible to know the mechanism that improves taste and texture parameters of the products through the implementation of new technologies (Ozuna et al., 2013). The fracture of muscle tissues caused by cavitation could be the reason that many studies have tried to elucidate the ability of high intense ultrasound to induce disruption of cell structure and to improve the textural and taste parameters in meat products including meat batter and dry‐cured ham in recent years (Alarcon‐Rojo et al., 2019; Contreras, Benedito, Quiles, Lorenzo, Fulladosa, & Garcia‐Perez, 2020; Li et al., 2015). It has been reported that ultrasound treatments show a great effect on protein stability and proteolytic enzymes activities related to disruption of myofibril structure leading to a higher degradation of muscle proteins (Stadnik et al., 2008; Lopez‐Pedrouso, Perez‐Santaescolastica, Franco, Carballo et al., 2018).…”
Section: Non‐invasive Techniques Could Be the Potential Solution For ...mentioning
confidence: 99%
“…Contreras, Benedito, Quiles, Lorenzo, Fulladosa, & Garcia‐Perez et al. (2020) demonstrated that hardness increased by 102% and adhesiveness decreased by 55%, and the ham became less viscoelastic by the ultrasound‐assisted thermal treatment (600 W, 20 kHz, 50°C), compared with the samples of the control group. The decrease of adhesiveness of sliced dry‐cured ham could be attributed to the fact that thermal and ultrasonic cavitation break the connection of intramolecular hydrogen and cause the relaxation of the molecular structure and reduction of molecular node (Ahmadi et al., 2012).…”
Section: Non‐invasive Techniques Could Be the Potential Solution For ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The former is often used in food analysis technology to provide information on food’s physical and chemical properties, such as hardness, sugar content, acidity, etc (Demirdöven & Baysal, 2008). The latter can be used as an assisted processing method to improve the physical or chemical properties of food (McClements, 1995), especially in meat processing, such as beef (Kang et al, 2017; Zou et al, 2018), pork (Contreras et al, 2020), and chicken (Li et al, 2020). As a kind of mechanical wave, the propagation of an ultrasonic wave in a liquid medium will produce tiny bubbles.…”
Section: Introductionmentioning
confidence: 99%